Susceptibility Status of Phlebotomus papatasi and P. sergenti (Diptera: Psychodidae) to DDT and Deltamethrin in a Focus of Cutaneous Leishmaniasis after Earthquake Strike in Bam, Iran - A Aghaei Afshar; Y Rassi; I Sharifi; MR Abai; MA Oshaghi; MR Yaghoobi-Ershadi; H Vatandoost (Tehran University of Medical Sciences, 2011)
Background: The cutaneous leishmaniasis (CL) has been occurred in Dehbakri County, located 46 km of Bam District, Kerman Province since 2004-2005. Phlebotomus papatasi is an important vector of zoonotic cutaneous leishmanisis (ZCL) as well as sand fly fever and P. sergenti is considered as main vector of anthroponotic cutaneous leishmaniasis (ACL) in Iran. There are several measures for vector control with emphasizing on insecticides. The objective of this study was to determine the baseline susceptibility of leishmaniasis vectors to the DDT and deltamethrin in an endemic focus of CL in southern Iran. Methods: Baseline susceptibility tests were carried out on field collected strains of P. papatasi and P. sergenti and tested with WHO impregnated papers with DDT 4.0% and deltamethrin 0.05% in the focus of disease in Dehbakri County during summer 2010. The values of LT50 and LT90 were determined using probit analysis and regression lines. Results: The LT50 value of DDT 4.0% and deltamethrin 0.05% against P. papatasi was 20.6 and 13.6 minutes respectively. The same data for P. sergenti were ranged between 21.8 and 17.7 minutes. Conclusion: The results of tests will provide a guideline for implementation of vector control using pesticides such as impregnated bed nets, indoor residual spraying and fogging.